Synthesis and Structure of the Novel Mononuclear Copper(II) Complex of the Unsymmetrical Pyrimidine-Modulated Long-Chain Hexapyridylpentaamine Ligand - Ismayilova, S.Z.; Guliyeva, L.Sh.; Ismayilov, R.H.; Tagiyev, D.B.; Valiyev, F.F.; Yalcin, B.; Medjidov, A.A.; Huseynova, M.T.; Chien, Su.Y.; Lee, G.H.; Peng, Sh.M. (Eurasian Journal of Chemistry, 2025)
Through the pyrimidine-modulated hexapyridylpentaamine ligand N2-(pyridin-2-yl)-N6-(6-((6-((6-(pyrimidin- 2-ylamino)pyridin-2-yl)amino)pyridin-2-yl)amino)pyridin-2-yl)pyridine-2,6-diamine (H5N11-tpm), a new mononuclear copper(II) complex [Cu(H5N11-tpm)](ClO4)2 (1) were synthesized and structurally characterized. The single crystal X-ray analysis showed distorted trigonal bypyramidal geometry (Addison parameter value τ = 0.69) of the complex (1), which is well consistent with the “inverted type” of ESR spectra (g∥ < g⊥), measured magnetic susceptibility, and electronic spectroscopy studies. The equatorial copper-nitrogen distances (Cu–N(1) = 2.094(9) Å; Cu–N(5) = 2.045(9) Å; Cu–N(9) = 2.214(9) Å), along with the axial Cu–N distances (Cu–N(3) = 1.999(9) Å and Cu–N(7) = 2.001(9) Å), fall well within the range typically reported for Cu(II) complexes that incorporate this type of ligand. All Cu–N distances are short, ranging from 1.999(9) to 2.094(9) Å, which suggests a strong binding affinity of the chelating ligand. The monohelical H5N11-tpm ligand coordinates with the metal atom, exhibiting an all-anti conformation. The extensive hydrogen bonds were observed between the amino groups and uncoordinated perchlorate anions, resulting in the formation of a three-dimensional network (3D) of the complex. The synthesized complex has high potential for the creation of novel cholinesterase inhibitors since it contains a number of pyridine and pyrimidine rings.
Keywords: modulated oligo-α-aminopyridine ligand; long-chain ligand; copper complex; crystal structure; addison parameter; hydrogen bonds; spectroscopy; magnetic measurement